Answer:
h = 4x ^ 3 + 18
Step-by-step explanation:
The first thing you should know for this case is that the area of a triangle is given by:
A = (1/2) * (b) * (h)
Where,
b: base.
h: height.
Clearing the height we have:
h = ((2) * (A)) / (b)
Substituting the values
h = ((2) * (14x ^ 5 + 63x ^ 2)) / (7x ^ 2)
Simplifying the expression:
h = ((2) * (2x ^ 3 + 9))
h = 4x ^ 3 + 18
answer
an expression to represent its height is
h = 4x ^ 3 + 18
Answer:
whats the shape?
Step-by-step explanation:
Using the Pythagorean theorem:
6^2 + X^2 = 14^2
36 + x^2 = 196
X^2 = 196-36
x^2 = 160
x = SQRT(160)
x = 4 SQRT(10)
Or as a decimal:
x = 12.65 inches
Answer:
x=30
Step-by-step explanation:
6x+4x-6=24+9x
combine like terms
10x-6=24+9x
add 6 on both sides
10x=30+9x
subtract 9x on both sides
x=30
Hope this helps! :)
Answer: <em>3w+4b</em>
Step-by-step explanation:
<em>Take your given equation</em>
<em>w+w+w+b+b+b+b</em>
<em>There are 3 w's and 4 b's</em>
<em>Combine like terms</em>
<em>w+w+w=</em><em>3w</em>
<em>b+b+b+b=</em><em>4b</em>
<em>3w+4b</em>